A systematic review of training interventions addressing sexual violence against marginalized at-risk groups of women - Kouta, Christiana; Pithara, Christalla; Zobnina, Anna; Apostolidou, Zoe; Christodoulou, Josie; Papadakaki, Maria G.; Chliaoutakis, Joannes El (My University, 2015)
Women from marginalized groups working in occupations such as domestic work are at increased risk for sexual violence. Scarce evidence exists about training interventions targeting such groups. The article aims to identify community and workplace-based training interventions aiming to increase capacity among marginalized at-risk women to deal with sexual violence. A systematic review was applied. Inclusion criteria were English language published between 2003 and 2013; reporting on delivery and/or evaluation; focusing on any form of sexual violence; delivered to professionals, affected or at-risk women; targeting migrant, at-risk women or domestic workers. Data were extracted on the setting, content, evaluation process and target population. Four studies which focused on prevention or responding to sexual violence were included. One study provided sexual violence training to vulnerable female and one provided a HIV prevention intervention to marginalized women. Learning objectives included increasing knowledge around issues of sexual violence and/or gender and human rights, prevention and response strategies. Two studies aimed to train trainers. All studies conducted an outcome evaluation and two a process evaluation. It seems there is a gap on participatory empowerment training for marginalized women. Community train-the-trainer interventions are imperative to protect themselves and deal with the risk of sexual violence.
Keywords: Domestic workers; Public-health; Prevention; Harassment; Empowerment; Strategies; Literacy; Assault; Impact